Pemetaan Tingkat Kerawanan Kebakaran Hutan dan Lahan Menggunakan Information Value Model di Provinsi Kalimantan Barat - Perwira Putra Aghni; Muhammad Aziz Rohman; Yosua Wiba Aguntar; Agelliyah Juliani; Milya Alfah Ulul Albab; Anisa Dewi Ika Pertiwi; Fikqri Ardiansyah (Faculty of Forestry Universitas Gadjah Mada, 2023)
Mapping forest fires became one of the efforts to reduce the fire vulnerability. Spatial model development for fire vulnerability could employ a GIS-based information value model (IVM) that excels in predicting vulnerability by leveraging hotspot inventory data. However, this model remained relatively unexplored. This research aimed to develop a fire vulnerability model of peatland-dominated areas in West Kalimantan Province and identify biogeophysical factors that significantly influence fire vulnerability in the research area. The IVM employed hotspots, accessibility, land cover, distance to settlements, distance to rivers, soil types, peat types, and Normalized Difference Vegetation Index (NDVI) parameters. The results revealed that the medium hazard class dominated forest and land fire vulnerability in West Kalimantan Province (272,663 ha). In addition, the average annual hotspot intensity from 2012 to 2022 negatively correlated with annual rainfall. Factors such as the brackish water topogen peat type, podzolic-cambisol soil type, accessibility, shrub land cover, and NDVI collectively contributed to the high level of vulnerability.